The Influence of Long Carbon Chains on the Antioxidant and Anticancer Properties of N-Substituted Benzisoselenazolones and Corresponding Diselenides - Agata J. Pacuła-Miszewska; Magdalena Obieziurska-Fabisiak; Aneta Jastrzębska; Angelika Długosz-Pokorska; Katarzyna Gach-Janczak; Jacek Ścianowski (MDPI AG, 2023)
Organoselenium compounds are well-known for their numerous biocapacities, which result from the uniqueness of the selenium atom and the possibility of constructing heterorganic molecules that can mimic the activity of selenoenzymes, crucial for a multitude of important physiological processes. In this paper, we have synthesized a series of N-substituted benzisoselenazolones and corresponding diphenyl diselenides possessing lipophilic long carbon chains, solely or with additional polar insets: phenyl linkers and ester groups. Evaluation of their antioxidant and cytotoxic activity revealed an increased H2O2-reduction potential of diphenyl diselenides bearing N-octyl, ethyl N-(12-dodecanoate)- and N-(8-octanoate) groups, elevated radical scavenging activity of 2,2'-diselenobis(N-dodecylbenzamide) and a promising cytotoxic potential of N-(4-dodecyl)phenylbenzisoselenazol-3(2H)-one.